The Nineteenth-Century Italian Political Migration to the Lusophone - Calzavara, Dario; Cassino, Carmine (Mediterranean Journal of Social Sciences, 2012)
Italy has been a country both of emigration and immigration. In a past historical period, the nineteenth century Risorgimento,which brought about the Italian Unification, our country experienced a varied migration flood towards Europe and Americas. Apart fromthe Great Migration Wave at the end of the century, throughout the previous decades there were a remarkable number of Italian peoplewho left the country for political reasons. That mass departure was often concealed by the home-leaving rhetoric. That migration wasalso bound for the Lusophone world, on the Continent and overseas, namely Portugal and Brazil. The former was the destination ofliberal exiles in the first half of the century, escaping from the repression by the Restoration governments; the latter became a refuge forrepublicans, anarchists and socialists persecuted by the new Italian monarchy in the last quarter of the century. That migration was not apassive one, but, on the contrary, it gave an active contribution to the political debate in the host countries, accompanying them intoModern Times. This essay tries to enhance both different and common features of those flows, which were, however, characterized by acertain causal link.